2012
DOI: 10.2355/isijinternational.52.704
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism behind Brittle-to-ductile Transition Understood by the Interaction between a Crack and Dislocations

Abstract: Fundamental mechanism governing the fracture toughness of materials is reviewed in terms of a concept of the interaction between a crack and dislocations. The mechanism behind brittle-to-ductile transition (BDT) is demonstrated using a simple model based on dislocation dynamics and the theory of cracktip shielding by dislocations. The effects of dislocation mobility as well as dislocation sources on the BDT behavior are discussed, which enables us to understand the various factors such as grain refinement infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] Ductility Large numbers of papers and reviews of multi-principle element alloys (MPEA) have demonstrated that near-equiatomic alloys with 4-6 elements have excellent strength and extremely high fracture toughness. [6][7][8][9][10][11][12][13][14][15] 2. Properties for outer space and energy solutions: Low-temperature strength From near-zero to hundreds of K, resilience of extreme temperature cycling, for long-distance radar acquisition and systems requiring a launch to Mars, as well as satellites require special multi-material designs.…”
Section: Properties For Infrastructurementioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Ductility Large numbers of papers and reviews of multi-principle element alloys (MPEA) have demonstrated that near-equiatomic alloys with 4-6 elements have excellent strength and extremely high fracture toughness. [6][7][8][9][10][11][12][13][14][15] 2. Properties for outer space and energy solutions: Low-temperature strength From near-zero to hundreds of K, resilience of extreme temperature cycling, for long-distance radar acquisition and systems requiring a launch to Mars, as well as satellites require special multi-material designs.…”
Section: Properties For Infrastructurementioning
confidence: 99%
“…It comes from the analogy of the study of GB decohesion by one of the authors (MY) 16 . We consider that the easier the bond-breaking occurs at a microcrack tip, the lesser the dislocations emit from there 14 , 15 , reducing fracture toughness and fracture stress in LME. The present study assumes that surface and GB adsorption itself does not affect the dislocation emission because the influence of liquid metal on dislocation is not evident theoretically and experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Those dislocations emitted cancel the stress intensity at the crack tip, resulting in the necessity for some extra amount of tensile stress for the crack to propagate. It is the origin of the increase in the facture toughness in terms of dislocation shielding [8].…”
Section: Introductionmentioning
confidence: 99%